Constitutional Review in the Middle East and North Africa - Schoeller-Schletter, Anja (Nahoststudien. Middle Eastern Studies, 2021)
Ten years after the Arab Spring, many parts of the Middle East and North Africa are struggling with the consequences of armed conflict, a balance of power tilted in favour of the executive and challenges to the rule of law. However, institutions charged with conducting constitutional review have been reformed substantially in most of the countries in those regions. A pioneer effort, this book offers first-hand insights by renowned practitioners and scholars into constitutional review in the Middle East and North Africa, discerning commonalities and differences from a comparative perspective. Structured along selected topics of interdisciplinary relevance-judicial independence, protection of fundamental rights, control of electoral law, and religious law in the constitutional order-the publication highlights the current state of constitutional review in the region: reference models, major develop-ments, challenges and trends. Anja Schoeller-Schletter is a lawyer and historian focusing on comparative constitutional law in North Africa and the Middle East. She designed the project behind this publication in her capacity as the Head of the Rule of Law Programme Middle East/North Africa in Beirut, Lebanon, a programme funded by the Konrad-Adenauer-Stiftung. Schlagworte